Dampak Tingkat Pendidikan, Partisipasi Angkatan Kerja, Struktur Ketenagakerjaan, dan Ketimpangan Pendapatan terhadap Populasi Kelas Menengah Indonesia - Bayu Try Haryanto; Herlitah Herlitah; Saparuddin M (Indo Publishing, 2026)
This study analyzes the influence of education level, labor force participation rate (LFPR), employment structure proxied by formal employment percentage, and income inequality on the middle-class population in Indonesia using the Error Correction Model (ECM) approach for the 2004–2025 period. The results indicate a cointegration relationship between variables with a significant Error Correction Term (ECT) of -0.6421, meaning that 64.21% of short-term imbalances can be corrected within one period toward long-term equilibrium. Education has no significant effect in the short run but shows a positive influence in the long run, confirming that education remains an important pathway for economic mobility. LFPR shows no significant effect in either the short or long run, indicating that increased labor participation without improved job quality is insufficient to expand the middle class. Formal employment has a positive and significant effect in the long run, suggesting that structural transformation toward the formal sector strengthens middle-class growth. Interestingly, the Gini index shows a positive and significant effect in the long run, reflecting that middle-class growth in developing countries can occur alongside rising inequality due to unequal access to economic opportunities. Overall, the dynamics of Indonesia's middle class are more determined by long-term structural transformation through education, formal employment expansion, and equitable access to economic opportunities, rather than short-term economic growth alone.